(untitled) (CIPEEX, 2026)
Introduction: Childhood sleep is crucial and disorders are common, relating to emotional, cognitive, behavioral, and cardiometabolic impairments, with family impact. Maternal/environmental factors such as mental health, routines, and sleep quality during pregnancy play a central role. Objective: To describe maternal habits and/or behaviors related to child sleep. Methods: Quantitative cross-sectional study with a convenience sample of 45 participants, caregiver-child (0–3 years old) at the pediatric outpatient clinic of UniEVANGÉLICA (Anápolis-GO), collected between March–July/2025; TCLE and ethical approval (CEP 6.824.631). The instruments used were the CSHQ (33 items/8 domains; cutoff point ≥41 for altered sleep) and the sociodemographic questionnaire, applied pre-consultation in a private room. A descriptive analysis was performed using SPSS®. Results: Among 45 mothers, the tables describe the sociodemographic profile, the predominance of cesarean sections (71.7%), low prenatal sleep guidance (84.8%), and limited partner involvement in the first 3 weeks (15.3%), with the most frequently cited difficulties related to breastfeeding, baby sleep, and colic. In addition, frequently disruptive sleep patterns (bed/room sharing), nighttime awakenings, and the need for help falling back to sleep highlight modifiable behaviors and the relevance of educational interventions. Conclusion: There is an immediate need for educational interventions on sleep hygiene, greater partner engagement, and systematic screening (e.g., CSHQ) in routine care. Despite the cross-sectional design and convenience sample, the findings offer practical guidance for family-centered care actions.